Philosophical Values in Tembang Macapat - Sutarjo Sutarjo (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
The Macapat song is a legacy of our ancestors which is full of beauty and philosophical values. In today's millennial era, the Macapat song is increasingly unknown to the public. The purpose of writing this paper is to reveal the philosophical values contained in the macapat song. The research location is in the city of Surakarta as the center and developer of Javanese culture, especially the macapat song. Data collection techniques by observing, listening, and taking notes. Data analysis used a qualitative descriptive method, which was to explain the philosophical value of the macapat song, which consisted of 11 (eleven) songs. Philosophical values describe the journey of the human life cycle from birth to death, obeying regulations and always maintaining the beauty of the universe.